Molecular laser isotope separation of 13C isotope by multi-photon dissociation of CF2HCl molecules with CO2 Laser - S. Beheshtipour; J. Karimi Sabet; R. Neshati; D. Esmaeilpour Ghoochani; A. Abbasi (مجله علوم و فنون هسته‌ای, 2023)
In this work, laboratory-scale laser isotope separation of 13C by isotope-selective multi-photon dissociation of CF2HCl gas molecules has been done. To do this, the pulses of a tunable TEA CO2 laser, which have been shortened using a plasma shutter, were focused inside the irradiation cell with fluence in 50 J/cm2. The irradiation cell was filled with 10-20 mbar of CF2HCl gas with CF2HCl:He ratio of 1:5 and 1:10. It has been shown that the abundance of 13C in C2F4 product of dissociation increases with decreasing of the gas pressure and the number of the incident pulses. In these experiments, the highest abundance of 13C isotope was obtained with CF2HCl: He ratio of 1:5 and ten mbar pressure of CF2HCl gas, irradiated by 1500 pulses with 50 J/cm2 fluences.